High magnesium mobility in ternary spinel chalcogenides. Issue 1 (December 2017) - Canepa, Pieremanuele; Bo, Shou-Hang; Sai Gautam, Gopalakrishnan; Key, Baris; Richards, William; Shi, Tan; Tian, Yaosen; Wang, Yan; Li, Juchuan; Ceder, Gerbrand
Abstract Magnesium batteries appear a viable alternative to overcome the safety and energy density limitations faced by current lithium-ion technology. The development of a competitive magnesium battery is plagued by the existing notion of poor magnesium mobility in solids. Here we demonstrate by using ab initio calculations, nuclear magnetic resonance, and impedance spectroscopy measurements that substantial magnesium ion mobility can indeed be achieved in close-packed frameworks ( 0.01–0.1 mS cm–1 at 298 K), specifically in the magnesium scandium selenide spinel. Our theoretical predictions also indicate that high magnesium ion mobility is possible in other chalcogenide spinels, opening the door for the realization of other magnesium solid ionic conductors and the eventual development of an all-solid-state magnesium battery. Low magnesium mobility in solids represents a significant obstacle to the development of Mg intercalation batteries. Here the authors show that substantial magnesium ion mobility can be achieved in close-packed ternary selenide spinel materials.